New species of Mecopodinae (Orthoptera, Tettigoniidae) from Tanzania - Hemp, Claudia (Zootaxa, 2020)
New species of Mecopodinae are described from Tanzanian mountain ranges. These are Apteroscirtus densissimus n. sp. from the Nguru Mountains, Gymnoscirtus corifterus n. sp. from the Udzungwa Mountains Nationalpark and a new subspecies of Phyloscirtus cordipennis Karsch, P. c. spinosus n. ssp. from the Nguru Mountains. Data on habitat are provided.